The Effect of Vitamin D3 Supplement with Football Training on Glucose, Insulin, Cortisol and ACTH Levels: Vitamin Supplement Study - Pancar, Zarife; Cinar, Vedat; Aydemir, Isa; Bulguru, Bedrettin (Lahore Medical Research Center Llp, 2021)
Background: Vitamin D-3 has an important role in the development of the musculoskeletal system, the protection of bone health and the effective functioning of the neuromuscular systems. Aim: In this study, it was aimed to investigate the effects of vitamin D-3 supplementation on glucose, insulin, cortisol and ACTH hormone given to young football players during four weeks in addition to training. Methods: 14 male volunteer athletes participated in the study. They were randomly divided into two groups as the control group (n:7) who continued their football training 5 days a week for four weeks, and the application group that received vitamin D-3 supplements in addition to football training (n:7). Resting blood samples were taken from the athletes participating in the study one day before and one day after the training and reinforcement applications. Glucose, insulin, cortisol and ACTH values were determined in the blood samples taken. Paired Samples t test was applied to determine the changes occurring within the group. Results: As a result of the analysis, there was no statistically significant difference between the glucose, insulin, cortisol and ACTH pre-test and post-test levels of the control group (p> 0.05), while the glucose and insulin levels of the group given vitamin D-3 supplement were found to be significantly different (p <0.05). In the intergroup analysis of the groups in terms of pre-test and post-test values, no significance was found in glucose, insulin, cortisol and ACTH values (p> 0.05). Conclusion: As a result of the research, it was found that vitamin D-3 supplementation applied in addition to football training caused differences in insulin and glucose levels among the biochemical parameters of young football players; It is thought that the use of D-3 together with exercise will produce results that improve public health and athlete performance.
Keywords: Vitamins; exercise; ACTH; cortisol